2017
DOI: 10.1177/1176934317735318
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of 11 Y Chromosome Short Tandem Repeat Markers among Malaysian Aborigines

Abstract: The conventional technique such as patrilocality suggests some substantial effects on population diversity. With that, this particular study investigated the paternal line, specifically Scientific Working Group on DNA Analysis Methods (SWGDAM)-recommended Y-STR markers, namely, DYS19, DYS385, DYS389I/II, DYS390, DYS391, DYS392, DYS393, DYS438, and DYS439. These markers were tested to compare 184 Orang Asli individuals from 3 tribes found in Peninsular Malaysia. As a result, the haplotype diversity and the disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Similarly, appropriate population data are needed before these two markers can be added as part of the DNA profiling procedures in Malaysia. Our survey using academic search engines such as Google Scholar and Scopus showed that the Y-STR [ 37 , 38 , 39 , 40 , 41 , 42 ] and mtDNA [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] population data are also lacking for many population groups in Malaysia (refer to Tables S2 and S3 ). Therefore, funding should be allocated urgently, not only for the establishment of mtDNA and Y-STR genotyping methodologies in RMP and KIMIA laboratories [ 4 ], but also for the development of autosomal STR, Y-STR, and mtDNA population databases for uncharacterized population groups in Malaysia.…”
Section: Dna Population Data For Casework and Paternity Testing Stmentioning
confidence: 99%
“…Similarly, appropriate population data are needed before these two markers can be added as part of the DNA profiling procedures in Malaysia. Our survey using academic search engines such as Google Scholar and Scopus showed that the Y-STR [ 37 , 38 , 39 , 40 , 41 , 42 ] and mtDNA [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] population data are also lacking for many population groups in Malaysia (refer to Tables S2 and S3 ). Therefore, funding should be allocated urgently, not only for the establishment of mtDNA and Y-STR genotyping methodologies in RMP and KIMIA laboratories [ 4 ], but also for the development of autosomal STR, Y-STR, and mtDNA population databases for uncharacterized population groups in Malaysia.…”
Section: Dna Population Data For Casework and Paternity Testing Stmentioning
confidence: 99%